Theban Graffito no. 1572 Rediscovered and Some New Texts from the “Valley of the Quarries” - Barwik, Mirosław (Zeitschrift für ägyptische Sprache und Altertumskunde, 2015)
Four hitherto unpublished graffiti from the “Vallée des Carrières”, on the northern borders of the Theban necropolis, are presented in the paper. Two of them are explicitly dated to year 16 (of Smendes or Paynudjem I?), and were written by the well-known scribe of the necropolis Ankhefenamun, son of Butehamun. There are good reasons to suppose that the other texts belong approximately to the same period, when extensive activity of the necropolis staff can be noted in the available sources. Some of the names provided by the present graffiti are known also from other sources dating to the very beginning of the XXI st Dynasty. However, the reason for the visit of an inspecting party (?) in this remote part of the Theban necropolis remains wholly unknown.